Effect of Spark Advance on a Gas Run Automotive Spark Ignition Engine - Ehsan, Md (Journal of Chemical Engineering, 2010)
Petrol engines can run on natural gas, with little modification. The combustion characteristics of natural gas is different from that of petrol, which eventually affects the engine performance. The performance of a typical automotive engine was studied running on natural gas, firstly at a constant speed for various loads and then at a constant load for a range of speeds and results were compared with performance using petrol. Variation of the spark advance, consisting of centrifugal and vacuum advance mechanisms, was investigated. Results showed some reduction in power and slight fall of efficiency and higher exhaust temperature, for natural gas. The air-fuel ratio for optimum performance was higher for gas than for petrol. This variation in spark requirement is mainly due to the slower speed of flame propagation for natural gas. For both the cases, the best power spark advance for natural gas was found to have higher values than petrol. This issue needs to be addressed during retrofitting petrol engines for running on natural gas. Journal of Chemical Engineering Vol.ChE 24 2006 42-49